PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK MEREK TERKENAL HUGO BOSS DARI PENIRUAN - Ida Ayu Ketut Artami; Kadek Januarsa Adi Sudharma; Made Widya Prasasti (VYAVAHARA DUTA, 2022)
For the sake of prestige, Indonesian people prefer tobuy well-known brand products. This then used by industry players to gain profits by committing trademark infringement against well-known international brands. One brand that is often being imitated is HUGO BOSS, which is famous in the field of fashion. The problem that arises from this background is how the procedure for registering international marks in Indonesia and the legal protection for HUGO BOSS trademark rights holders according to Law no. 20 of 2016 (MIG Law)?. Normative legal research is used in this research. Legal materials types used are, primary which is MIG Law; secondary; and tertiary are used. This research uses a case and legislation approach. The technique of analyzing legal materials is qualitative descriptive to describe regulation related to trademark rights, legal protection specifically for well- known marks systematically. The result is that the procedure for registering international marks in Indonesia is based on Article 52 of the MIG Law which is further regulated in the PP Madrid Protocol. Foreign parties wishing to register a trademark in Indonesia must submit a registration application to the international bureau and it will foward the application to the Minister. The legal protection given HUGO BOSS is preventive legal protection, by registering a mark as regulated in the MIG Law, PP Madrid Protocol and other regulation regarding tradenark. HUGO BOSS also gets repressive legal protection, by filing a trademark cancellation lawsuit to the Commercial Court and submitting an appeal to the Supreme Court.